Climate change impacts and its implications on future water resource management in the Meghna Basin. (April 2016) - Masood, Muhammad; Takeuchi, Kuniyoshi
Graphical abstract: Highlights: The higher probability of strong annual peak flow is expected in the future. The monsoonal peak flows are expected to come about 1 ∼ 1.5 month earlier. The findings lead to higher possibility of earlier flash flood in the future. Inhabitants living in lower areas, particularly farmers will be more vulnerable. The findings will have significant implications for water resource management. Abstract: Copious precipitation in the Meghna Basin has remarkable consequences for floods in the north-eastern region of Bangladesh. In addition, due to climate change more frequent extreme precipitation may also increase the frequency and intensity of flash floods. In this study, a hydrologic model H08 has been applied over the basin at a relatively fine grid resolution (10 km). The impacts of climate change are assessed by using the super-high-resolution MRI-AGCM3.2S with A1B scenario through three time-slice experiments; the base-period (1979–2003), the near-future (2015–2039), and the far-future (2075–2099) periods. This study investigates the spatio-temporal changes and the changes in the frequency of precipitation and runoff with different magnitude ranges and finds the implications for water resources management under climate change. Results show that, (a) the projected maximum increment of mean annual precipitation (runoff) is +23% (+34%) and +31% (+39%) during the near-future and the far-future, respectively, (b) the projected increment of median value of monthly discharges at basin outlet is significantly high in wet period (May-July), ranging from 38 to 44% and 25–104% in the near-future and the far-future, respectively. Moreover, the monsoonal peaks are expected to come about 1 ∼ 1.5 month earlier, which ultimately lead to higher possibility of earlier flash flood in the future. This anticipated higher increment in peak discharge as well as future shifting of seasonal cycle of river discharge will have significant implications for agriculture and flood disaster management. Findings will also contribute to enhance water resource management in the basin and improve the design of adaptive measures.